1996
DOI: 10.1111/j.1600-0781.1996.tb00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual reduction of solar UV exposure to the facial area of outdoor workers in Southeast Queensland by wearing a hat

Abstract: The total annual exposure to erythemally effective UVR was estimated for average work situations in a high exposure environment, viz, farm workers in Southeast Queensland (27.5 degrees S), and the effect of hat usage was examined. If no sun protection is used, the annual erythema exposures for this group of workers at three facial sites forehead, nose and cheek are 40, 57 and 34 J.cm-2 respectively. If a hat is worn throughout the year, the exposures are reduced to 6, 19 and 20 J.cm-2, respectively. The mean r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 4 publications
1
43
0
2
Order By: Relevance
“…By making relative comparisons, the dependence on the age of the individual can be removed (27,28). This technique was recently applied to calculate relative basal and squamous cell carcinoma risk for golfers in southern Queensland compared to office workers (10).…”
Section: Introductionmentioning
confidence: 99%
“…By making relative comparisons, the dependence on the age of the individual can be removed (27,28). This technique was recently applied to calculate relative basal and squamous cell carcinoma risk for golfers in southern Queensland compared to office workers (10).…”
Section: Introductionmentioning
confidence: 99%
“…Outras formas de proteção recomendadas e que aparecem nos estudos sobre o tema são o uso de chapéus e o hábito de buscar a sombra quando no deslocamento ou permanência em áreas ensolaradas. No entanto, o efeito positivo oriundo da utilização de chapéus, por exemplo, ainda é contraditório na literatura 14,15,16 .…”
Section: Introductionunclassified
“…Some studies were found that addressed outdoor workers in Australia (Dobbinson and Knight, 2001;Parisi et al, 1999;Kimlin et al, 1998;Airey et al, 1997;Green et al, 1996;Wong et al, 1996;Girgis et al, 1994;Borland et al, 1991). These studies were carried out mostly in Queensland, with two in Victoria and another in NSW.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Outdoor workers who participated included farmers, Telecom lines staff, and tradespersons. The focus of five of these studies was exposure to UVR (Parisi et al, 1999;Kimlin et al, 1998;Airey et al, 1997;Green et al 1996;Wong et al, 1996) with the remaining studies focusing on the effects of an interventions on outdoor workers' sun protective behaviour (Girgis et al, 1994;Borland et al, 1991) and organisational change (Dobbinson and Knight, 2001). No study was found that had surveyed outdoor workers in NSW to assess their knowledge and sun protective behaviour associated with their risk of skin cancer.…”
Section: Literature Reviewmentioning
confidence: 99%